Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Para resolver la ecuación [tex]\(7(2m + 3) - 5m = 2(4m + 8) + 9\)[/tex], sigamos estos pasos detalladamente:
1. Distribuir los números dentro de los paréntesis:
[tex]\[ 7(2m + 3) - 5m = 2(4m + 8) + 9 \][/tex]
Aplicamos la propiedad distributiva a ambos lados:
[tex]\[ 7 \cdot 2m + 7 \cdot 3 - 5m = 2 \cdot 4m + 2 \cdot 8 + 9 \][/tex]
Esto se convierte en:
[tex]\[ 14m + 21 - 5m = 8m + 16 + 9 \][/tex]
2. Simplificar cada lado de la ecuación:
[tex]\[ 14m + 21 - 5m = 8m + 25 \][/tex]
Combinamos los términos semejantes:
[tex]\[ 9m + 21 = 8m + 25 \][/tex]
3. Mover todos los términos con [tex]\(m\)[/tex] a un lado de la ecuación:
Restamos [tex]\(8m\)[/tex] de ambos lados:
[tex]\[ 9m - 8m + 21 = 25 \][/tex]
Esto nos da:
[tex]\[ m + 21 = 25 \][/tex]
4. Aislar la variable [tex]\(m\)[/tex]:
Restamos 21 de ambos lados:
[tex]\[ m = 25 - 21 \][/tex]
Simplificamos:
[tex]\[ m = 4 \][/tex]
Por lo tanto, la solución a la ecuación [tex]\(7(2m + 3) - 5m = 2(4m + 8) + 9\)[/tex] es [tex]\(m = 4\)[/tex].
1. Distribuir los números dentro de los paréntesis:
[tex]\[ 7(2m + 3) - 5m = 2(4m + 8) + 9 \][/tex]
Aplicamos la propiedad distributiva a ambos lados:
[tex]\[ 7 \cdot 2m + 7 \cdot 3 - 5m = 2 \cdot 4m + 2 \cdot 8 + 9 \][/tex]
Esto se convierte en:
[tex]\[ 14m + 21 - 5m = 8m + 16 + 9 \][/tex]
2. Simplificar cada lado de la ecuación:
[tex]\[ 14m + 21 - 5m = 8m + 25 \][/tex]
Combinamos los términos semejantes:
[tex]\[ 9m + 21 = 8m + 25 \][/tex]
3. Mover todos los términos con [tex]\(m\)[/tex] a un lado de la ecuación:
Restamos [tex]\(8m\)[/tex] de ambos lados:
[tex]\[ 9m - 8m + 21 = 25 \][/tex]
Esto nos da:
[tex]\[ m + 21 = 25 \][/tex]
4. Aislar la variable [tex]\(m\)[/tex]:
Restamos 21 de ambos lados:
[tex]\[ m = 25 - 21 \][/tex]
Simplificamos:
[tex]\[ m = 4 \][/tex]
Por lo tanto, la solución a la ecuación [tex]\(7(2m + 3) - 5m = 2(4m + 8) + 9\)[/tex] es [tex]\(m = 4\)[/tex].
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.